Prognostic Value of the Immunohistochemical Expression of RAD51 and BRCA2 in Gastric Adenocarcinoma. (March 2022) - Pádua, Joel Del Bel; Mariano, Carolline Fontes Alves; Fabro, Alexandre Todorovic; Tirapelli, Daniela Pretti da Cunha; Sankarankutty, Ajith Kumar; dos Santos, José Sebastião; Brunaldi, Mariângela Ottoboni
Current scientific literature lacks data on the prognostic value of the expression of RAD51 and BRCA2 in gastric adenocarcinoma. Therefore, we aimed to evaluate those and other homologous recombination-related proteins (ATM, ATR, BRCA1, CHK2, γH2AX, p53) in gastric cancer, assessing their correlation with clinical prognosis. Paraffin-embedded samples were obtained from surgical specimens collected in total or subtotal gastrectomy procedures. Between 2008 and 2017, 121 patients with advanced gastric adenocarcinoma underwent surgical resection and were included in this study. Negativity for nuclear RAD51 correlated with vascular invasion, lymph node metastasis, larger tumor size, and lower overall survival and disease-free survival in univariate analysis. However, nuclear RAD51-negative cases presented better response rates to adjuvant therapy than the positive ones. Nuclear ATR negativity correlated with larger tumor size and a higher histological grade. Positivity for ATM was associated with more prolonged disease-free survival. Positivity for nuclear BRCA2 correlated with lower overall survival and diffuse histological type, whereas its high expression was associated with vascular invasion. Nevertheless, tumors positive for nuclear BRCA2 were more frequently low grade in the intestinal histological type. Our findings indicate that RAD51 and BRCA2 are valuable immunohistochemical prognostic markers in gastric adenocarcinoma.